Flexible quality of service model for wireless body area sensor networks. Issue 1 (16th March 2016) - Liao, Yangzhe; Leeson, Mark S.; Higgins, Matthew D.
Abstract : Wireless body area sensor networks (WBASNs) are becoming an increasingly significant breakthrough technology for smart healthcare systems, enabling improved clinical decision‐making in daily medical care. Recently, radio frequency ultra‐wideband technology has developed substantially for physiological signal monitoring due to its advantages such as low‐power consumption, high transmission data rate, and miniature antenna size. Applications of future ubiquitous healthcare systems offer the prospect of collecting human vital signs, early detection of abnormal medical conditions, real‐time healthcare data transmission and remote telemedicine support. However, due to the technical constraints of sensor batteries, the supply of power is a major bottleneck for healthcare system design. Moreover, medium access control (MAC) needs to support reliable transmission links that allow sensors to transmit data safely and stably. In this Letter, the authors provide a flexible quality of service model for ad hoc networks that can support fast data transmission, adaptive schedule MAC control, and energy efficient ubiquitous WBASN networks. Results show that the proposed multi‐hop communication ad hoc network model can balance information packet collisions and power consumption. Additionally, wireless communications link in WBASNs can effectively overcome multi‐user interference and offer high transmission data rates for healthcare systems.